2015
DOI: 10.1155/2015/835204
|View full text |Cite
|
Sign up to set email alerts
|

Statins in Asthma: Potential Beneficial Effects and Limitations

Abstract: Asthma's sustenance as a global pandemic, across centuries, can be attributed to the lack of an understanding of its workings and the inability of the existing treatment modalities to provide a long lasting cure without major adverse effects. The discovery of statins boosted by a better comprehension of the pathophysiology of asthma in the past few decades has opened up a potentially alternative line of treatment that promises to be a big boon for the asthmatics globally. However, the initial excellent results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 132 publications
0
25
0
Order By: Relevance
“…There have been a number of studies and reviews that have examined the efficacy of statins in asthma, as these cholesterol-lowering agents have anti-inflammatory and anti-oxidant effects and are a mainstay of risk reduction in cardiovascular disease (48)(49)(50). However, statins have not been demonstrated to be consistently effective for the treatment of asthma, which may reflect a variety of factors that have been reviewed elsewhere (48). We have found that serum cholesterol levels are not associated with blood eosinophil counts, serum periostin levels, or FEV 1 , which suggests that modifying cholesterol levels alone may not be sufficient to manage asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies and reviews that have examined the efficacy of statins in asthma, as these cholesterol-lowering agents have anti-inflammatory and anti-oxidant effects and are a mainstay of risk reduction in cardiovascular disease (48)(49)(50). However, statins have not been demonstrated to be consistently effective for the treatment of asthma, which may reflect a variety of factors that have been reviewed elsewhere (48). We have found that serum cholesterol levels are not associated with blood eosinophil counts, serum periostin levels, or FEV 1 , which suggests that modifying cholesterol levels alone may not be sufficient to manage asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…However, results from these RCTs have produced equivocal and at times conflicting results. While asthmatics may benefit from added statin therapy by reducing airway inflammation, consistent improvement in lung function or symptoms has not been definitively established in these RCTs [51,52,55]. Although these results can be characterized as equivocal at best [57–60], statins did reduce sputum eosinophils [54,55], macrophages [56], leukotriene B 4 , sputum proinflammatory cytokines and growth factors [53].…”
Section: The Mevalonate Pathway Statins and Relevance To Asthmamentioning
confidence: 99%
“…Indeed, no RCTs have investigated patients with severe asthma or determined the most effective statin or statin class to use. These RCTs also utilized relatively small sample sizes (<75 participants), had varied study designs, used different corticosteroid treatment regimens, and administered oral statin doses typically used to treat hyperlipidemia [95]. Importantly, these clinical trials did not assess primary end-points such as acute exacerbation requiring systemic corticosteroid treatment, ED visits, hospitalizations, and/or respiratory failure [87].…”
Section: The Mevalonate Pathway Statins and Relevance To Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…The low levels of statins in the lungs are unfavourable since the main pharmacological targets of statins are the airway epithelium, alveolar macrophages, fibroblasts, endothelial cells and inflammatory cells which are responsible for the inflammatory cascade in chronic airway diseases. Other Additional issues that need to be considered include the different types of statin which may exert variousanti-inflammatory efficacies, the required optimal dose to be delivered to the airways for effective therapeutic effectoutcomes, the duration of statin treatment required before therapeutic effects could can be observed, whether statins are better as an alternative sole therapy or as an adjunct/combination with other therapies, and finally if statins are only eaffective in a particularspecific patient population phenotype[105].…”
mentioning
confidence: 99%